The pathogenesis of diabetic kidney disease and the therapeutic potential of bioactive substances - Chen, Yan; Li, He; Dai, Qiuju; Tan, Zhen; Wu, Huihui; Xu, Zhiyi; Wang, Guangwei; Fang, Yang; Luo, Jie; Yu, Chenghao; Huang, Mingliang; Peng, Cheng (Frontiers in Pharmacology, 2025)
Diabetic kidney disease (DKD), one of the common complications of diabetes, is a major contributor to chronic kidney disease (CKD) worldwide. Due to its high incidence and disability rates, DKD poses a serious threat to human health and represents a significant public health burden. Although current treatments, such as angiotensin-converting enzyme (ACE) inhibitors, are available, they remain limited in pharmacological effects. Medicinal plants are valuable resources for drug development, and their bioactive compounds have attracted considerable attention for their therapeutic potential in DKD. In this review, we systematically searched major scientific databases (e.g., PubMed) for studies published within key timeframes relevant to each topic. Keywords such as “DKD and oxidative stress” and “diabetic nephropathy and bioactive substances” were used to identify high-quality original research and review articles closely aligned with the theme of this work. Based on the selected literature, we summarize the pathogenic mechanisms of DKD and elucidate the therapeutic effects and mechanisms of bioactive substances—including polyphenols, peptides, polysaccharides, and flavonoids—in its treatment. A comparative analysis is also presented to provide a foundation for future pharmacological research on DKD.